The archaeal protein SepF is essential for cell division in Haloferax volcanii - Phillip Nußbaum (Nature Portfolio, 2021)
In most bacteria, cell division depends on tubulin homolog FtsZ and other proteins, such as SepF. Cell division in many archaea also depends on FtsZ. Here, Nußbaum et al. show that a SepF homolog plays important roles in cell division in Haloferax volcanii, a halophilic archaeon that has two FtsZ homologs.